Non-academic L2 Users: A Neglected Research Pool in ELT in Iran - Talebinezhad, Mohammad Reza; Sadeghi Beniss, Aram Reza (Linguistik Online, 2005)
English Language Teaching (ELT) articles are published and their results are relied on without delving into their methodological credibility. A research study cannot be considered valid unless its population is precisely determined and defined. This article shows the considerable size of non-academic English learners in Iran and argues that the population in ELT research should not be limited only to university and school students who are easily accessible but it should also include the sizeable non-academic sector. To do this, 170 PhD dissertations and MA theses in TEFL were randomly selected. The result showed that only less than 9% of the participants belonged to non-academic sector. The article also argues that there is wrong overgeneralization of even the existing ELT academic researches to non-academic situation. Finally it compares academic and non-academic English learners to show how the latter are highly motivated to learn.